2018
DOI: 10.3390/jintelligence6010012
|View full text |Cite
|
Sign up to set email alerts
|

Intraindividual Variability across Neuropsychological Tests: Dispersion and Disengaged Lifestyle Increase Risk for Alzheimer’s Disease

Abstract: Objective : Increased intraindividual variability (IIV) in function has been linked to various age-related outcomes including cognitive decline and dementia. Most studies have operationalized IIV as fluctuations across trials (e.g., response latencies) for a single task, with comparatively few studies examining variability across multiple tasks for a given individual. In the present study, we derive a multivariable operationalization of dispersion across a broad profile of neuropsychological measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 38 publications
2
27
0
Order By: Relevance
“…Individual dispersion profiles are obtained by using a regression technique, which computes iSD scores from standardized test scores ( Christensen et al, 1999 ; Hultsch et al, 2002 ; Cole et al, 2011 ; Halliday et al, 2018 ). Test scores of interest (TMT-A, TMT-B/TMT-A, Digit Span Forward, Digit Span Backward, Verbal Fluency Phonemic, Verbal Fluency Semantic, Word Span average across trials 4, 5, and 7) were initially regressed on linear age trends across all participants, then the resulting residuals from these models were standardized as z-scores ( M = 0, SD = 1), with individual iSDs subsequently computed across these z -scores.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Individual dispersion profiles are obtained by using a regression technique, which computes iSD scores from standardized test scores ( Christensen et al, 1999 ; Hultsch et al, 2002 ; Cole et al, 2011 ; Halliday et al, 2018 ). Test scores of interest (TMT-A, TMT-B/TMT-A, Digit Span Forward, Digit Span Backward, Verbal Fluency Phonemic, Verbal Fluency Semantic, Word Span average across trials 4, 5, and 7) were initially regressed on linear age trends across all participants, then the resulting residuals from these models were standardized as z-scores ( M = 0, SD = 1), with individual iSDs subsequently computed across these z -scores.…”
Section: Methodsmentioning
confidence: 99%
“…Reduced dispersion (cognitive de-differentiation) has been reported as a function of age across measures of speed of processing, working-memory, verbal fluency and lexical decision both in cross-sectional and longitudinal studies ( Li et al, 2004 ; Rabbitt et al, 2004 ). However, more recent studies have reported the opposite pattern, namely an increase in dispersion with increasing age ( Hultsch et al, 2000 ; Sosnoff and Newell, 2006 ; Hilborn et al, 2009 ; Halliday et al, 2018 ). These inconsistent results may derive from (i) differences in neuropsychological batteries, (ii) analysis adopted to compute dispersion index, and/or (iii) demographic differences in age groups across studies.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations